Division of childcare policy actors under health-oriented goals: thematic analysis of China’s policy texts from the social constructionist perspective - Li, Linan; Li, Junyu (Frontiers in Public Health, 2024)
BackgroundEnsuring child health, as a key objective of global childcare policies, requires coordinated efforts between the government, social organizations and communities, institutions, and families. Despite China’s progress in comprehensive childcare policy development, rapid economic growth, and urbanization, challenges persist, such as urban–rural disparities and unequal resource distribution, highlighting the need for effective collaboration between policy actors.MethodsTo collect textual data, this study searched for prefectural-level childcare policy texts issued since 2019 on government websites and legal databases, ultimately identifying 224 documents for analysis. This study reviewed the literature on the impact of childcare policies on child health and identified the enhancement of childcare quality as a current research focus. This study then conducted a content analysis using Nvivo12 Plus software and coded and analyzed the childcare policy content. Finally, it applied social construction theory to interpret the policy documents.ResultsChildcare policies were centered around child health and formed a responsibility and accountability framework between the government, social organizations and communities, institutions, and families, whose action shares accounted for 38.9, 22.89, 29.05, and 9.16%, respectively. The development of childcare institutions was a key aspect of the defamilialization trend. Compared to other policy actors, institutions played a larger role in child health policy aspects such as safety management (12.97%), health and hygiene (8.56%), and scientific parenting (10.93%).ConclusionWithin China’s health-oriented framework, the refamilialization and defamilialization processes coexist in terms of childcare policies, and limited community-based childcare resources extend beyond the family. The participation of diverse policy actors in China’s childcare system is expected to persist, underscoring the increased need to enhance the policy actors’ negotiation skills and bolster community-based childcare services in the future.